Managing silence in workplaces - Vemuri, Sivaram (Bingley, U.K. : Emerald Publishing Limited, 2019)
Silence within the workplace restricts change, transformation and the innovation of organizations. It can also be detrimental to the health and well-being of individual employees.Managing Silence in Workplaces investigates the costs of silence to the individual, the organization and society at large. In examining the coexistence of voice, noise and silence, the book demonstrates that management of silence is not possible in isolation of these other concepts. Adopting an interdisciplinary approach towards managing silence in workplaces, the book traces individual employee silence as movements in five zones of silence - hope, indifference, helplessness, hopelessness and exit.Looking at both the employer and employee perspectives, Sivaram Vemuri advocates the need to nurture hope to better manage and address the costs of silence to the individual employee and the organization. By incorporating examination of ethics into the management of silence in the workplace, the book proposes that silence can be managed better by the resolute pursuit of consciousness and breaking down the communication of real and imaginary barriers in workplaces and in the minds of the employees of organizations. It is an illuminating book for practitioners and researchers working within human resources management, as well as managers of organizations in any field.
Prelims -- 1. The silent killer -- 2. Paying attention to silence -- 3. Conceptualising silence -- 4. Types of silence in the workplace -- 5. Measuring silence in the workplace -- 6. Application in real-world contexts -- 7. Conclusions -- References -- Index.
Includes bibliographical references and index.
Keywords: Personnel management; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management